Research progress of microvascular development in bronchopulmonary dysplasia - Jiaxin Zhang; Weiwei Du; Zongli Zhang; Tao Li; Xingchao Li; Shibing Xi (Pediatric Investigation)
ABSTRACT Bronchopulmonary dysplasia (BPD) is a chronic lung disease that arises during the neonatal period, and its underlying mechanisms are still not fully understood. The disorder of microvascular development plays a significant role in the development of BPD. This article presents a comprehensive review of the advancements made in understanding the mechanisms and treatment approaches related to microvascular development in the pathogenesis of BPD.